SOME CURRENT PROBLEMS IN ADMINISTERING THE RETAIL INVENTORY METHOD. - Schmalz, Carl N. (The Accounting Review, 1934)
This article discusses some current problems in administering the retail inventory method. The retail method was created to meet the inventory valuation problems of department and specialty, women's apparel, stores, which constitute a distinct type of trading enterprise with valuation problems quite different from those of manufacturers, public utilities, railroads, and other kinds of business organization, and even from those of some other types of retail concern. Department and specialty stores buy and sell merchandise, but for the most part do not compound or process merchandise. The retail inventory method involves the recording of beginning inventories and purchases at both cost and retail prices, the marking of prices on the goods at retail only, the recording of all price changes, the taking of inventories at retail prices only, and the reduction of inventory valuations to cost basis by use of the avenge mark-up percentage. The keeping of complete records, of course, implies that a book inventory may be arrived at any time.